Surgical treatment of a chronic foveal retinal detachment combined with staphyloma, foveoschisis, and macular hole - Efthymios Karmiris; Evangelia Chalkiadaki; Ourania Fydanaki; Michael Apostolopoulos (Oman Journal of Ophthalmology, 2023)
To present a case of anatomical success and visual improvement after the treatment of a long-standing foveal retinal detachment in a staphylomatous myopic eye with foveoschisis and macular hole. A 60-year-old woman with high myopia presented with foveoschisis and a lamellar macular hole in her right eye. After 2 years of follow-up without deterioration, her eye developed a full-thickness macular hole and a foveal retinal detachment which caused a severe reduction in visual acuity. However, the patient had no surgical treatment for her condition at that time. Vitrectomy was performed 2 years after the retinal detachment formation. Regardless of the longstanding detachment, anatomical success, and visual improvement were evident after the surgery. Despite a 2-year longstanding foveal detachment on a highly myopic eye with foveoschisis and macular hole, surgical repair could still be satisfactory.